Digital Visual Effects in Cinema : The Seduction of Reality - Prince, Stephen, 1955-2020 (Book collections on Project MUSE., 2012)
"Stephen Prince argues for an understanding of digital technologies as an expanded toolbox, available to enhance both realist films and cinematic fantasies. He offers a detailed exploration of each of these tools, from lighting technologies to image capture to stereoscopic 3D. Integrating aesthetic, historical, and theoretical analyses of digital visual effects, Digital Visual Effects in Cinema is an essential guide for understanding movie-making today"--Provided by publisher.